Pengaruh Media Sosial Terhadap Perkembangan Bahasa Remaja - Khairunisa Anggraini; Usiono (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
The purpose of this research is to find out the problems of adolescent language development influenced by social media. This research method uses the literature study method.b Data collection is done by finding sources and constructing from various sources such as books, journals and research that has been done. The influence of social media on adolescent language development is very important for Indonesian society so that today's teenagers can speak politely.